A customized assessment tool to differentiate safety and hygiene control practices in emerging dairy chains. (May 2020) - Ledo, James; Hettinga, Kasper A.; Luning, Pieternel A.
Abstract: In emerging dairy chains, inconsistent product quality and safety are recurring issues. The need for improvement in hygiene and safety control practices to meet rapidly growing demands for dairy products quality and safety is imperative. However, existing assessment tools do not consider specific situations in emerging dairy chains, where practices are often performed below standard requirements, which presents an inaccurate picture when these tools would be used. This study presents the development of a customized tool to assess and differentiate levels of safety and hygiene control practices in emerging dairy chains. The tool consists of indicators to analyse control practices and four corresponding grids to assess and differentiate the levels of the safety and hygiene control practices at the farm, during transportation, milk collection, and at local retail points crucial for microbial and chemical (i.e. aflatoxin) safety. The customized tool was piloted in Tanzania to assess on-farm practices, as an example of an emerging dairy chain, using interviews, farm visits and audio-visual assisted observations. Thirty-eight small and three large-scale farmers were interviewed, and their control practices observed. The responses were scored based on the grids and the scores were used for data analysis to identify patterns among the farmers. Overall, the customized assessment tool was able to accurately differentiate safety and hygiene practices of the farmers into three distinct clusters. The majority of the small-scale dairy farmers were performing practices at poor to basic level with very few practices at an intermediate level. The large-scale farmers were operating mainly at intermediate to standard level but with basic level performance on milk safety monitoring method, udder and teat care, and personal hygiene practices. Overall, incremental changes are required for on-farm practices to adequately mitigate microbial and aflatoxin contamination of fresh milk. Furthermore, the obtained profiles on farmers safety and hygiene control practices provide input for the development of training programs tailored to the knowledge and skills needs of groups of farmers with similar performance levels. Further research is needed to provide insight into the relationship between the level of control practices and milk safety outcomes. Highlights: Recurring quality and safety issues in emerging dairy chains demand attention. Developed and validated a customized tool to assess safety and hygiene control practices. The customized tool accurately differentiated dairy farmers based on their practices. Performance profiles provide a basis for incremental changes in farmers' practices. The tool can provide inputs for dedicated training on safety and hygiene practices.